NA-LINK I (Linking Past and Present in the North Atlantic) - Cruise No. MSM38 - May 07 - June 05, 2014 Cadiz (Spain) - St. John's (Canada) - Kieke, Dagmar; Breckenfelder, Tilia; Büsing, Merle; Diekmann, Thorben; Gerken, Jan; Hauck, Dennis; Horn, Myriel; Hüsener, Matthias; Leiner, Milena; Papp, Dennis; Raschke, Michaela; Roessler, Achim; et al. (DFG-Senatskommission für Ozeanographie, 2015)
Cruise MSM38 dealt with investigating the recent changes in the water mass structure and the circulation system in the western subpolar North Atlantic. In conjunction with the subsequent cruise MSM39, both cruises were dedicated to linking past and present changes in the North Atlantic with MSM38 focusing on modern time scales and MSM39 on paleoceanographic variations. A regional focus of cruise MSM38 was on revisiting two hydrographic repeat lines following the course of the Mid-Atlantic Ridge (MAR) along its western flank as well as the approximate latitude of 47°N in the Newfoundland Basin and servicing different longterm deep-sea observatories in the form of moorings and bottom-mounted inverted echo-sounders equipped with pressure sensors (PIES). While all moorings could be successfully deployed (four along the MAR-line, one in the Deep Western Boundary Current (DWBC) region off Flemish Cap), the recovery of two moorings (FFZ-2 next to the MAR, BM-26/1 in Flemish Pass) failed, presumably due to material failure in the mooring components or fishery activity. Two PIES were successfully recovered and redeployed; data from all eight installed PIES could be successfully received via acoustic data telemetry. Despite water samples necessary to calibrate conductivity and oxygen sensors of the conductivity-temperature-depth/oxygen (CTD/O) profiling system, particular samples with the focus on chlorofluorocarbons (CFC) were obtained at selected stations next to the MAR and in the region of the DWBC east of Flemish Cap. Additional samples with the focus on carbon and oxygen isotopes were generally obtained on every second station; the spatial resolution was, however, coarser along the MAR-line. Continuous and station-based velocity data were obtained from vessel-mounted and lowered Acoustic Doppler Current Profilers (ADCP). Fair weather conditions during major parts of the cruise, no limitations due to the presence of ice, and economic field work allowed further hydrographic field work in the DWBC region around Flemish Cap. Apart from a test-station, 128 CTD/O- and ADCP-stations have been carried out in total. : MARIA S. MERIAN-Berichte